Fifty years is nothing... easier said - Fonseca Corrales, Elizabeth (2026)
Drawing from Elizabeth Fonseca Corrales’s lecture, this article offers a journey through the past fifty years of the Revista de Historia. The article also highlights the journal’s role in the history discipline in Costa Rica and Central America. The analysis is organized into two main stages. The first focuses on the period 1975–1985, examining the journal’s challenging beginnings at the National University (UNA), overcoming the crises that threatened its continuity. The second stage examines the period beginning in 1985, marked by the consolidation of the project, driven by a 1986 co-publishing agreement between the National University and the University of Costa Rica. The author shares her 17-year experience as an editor-in-chief, detailing the evolution of editorial processes and the technological and thematic challenges encountered. Finally, she reflects on the termination of the inter-university agreement in 2012 and on the journal’s legacy in shaping a community of historians in the region.